2018
DOI: 10.1111/nph.15272
|View full text |Cite
|
Sign up to set email alerts
|

The requirement for calcification differs between ecologically important coccolithophore species

Abstract: Summary Coccolithophores are globally distributed unicellular marine algae that are characterized by their covering of calcite coccoliths. Calcification by coccolithophores contributes significantly to global biogeochemical cycles. However, the physiological requirement for calcification remains poorly understood as non‐calcifying strains of some commonly used model species, such as Emiliania huxleyi, grow normally in laboratory culture.To determine whether the requirement for calcification differs between coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 74 publications
3
52
0
1
Order By: Relevance
“…Some structural diversity was observed in the polysaccharide layers between species. C. braarudii exhibited a granular polysaccharide layer with distinct regularly spaced areas in which staining was absent (Figure 2A), as observed previously (Walker et al, 2018). These regular ellipsoidal regions likely correspond to the position of the coccoliths.…”
Section: Localization Of Extracellular Polysaccharides Using the Fluosupporting
confidence: 82%
See 2 more Smart Citations
“…Some structural diversity was observed in the polysaccharide layers between species. C. braarudii exhibited a granular polysaccharide layer with distinct regularly spaced areas in which staining was absent (Figure 2A), as observed previously (Walker et al, 2018). These regular ellipsoidal regions likely correspond to the position of the coccoliths.…”
Section: Localization Of Extracellular Polysaccharides Using the Fluosupporting
confidence: 82%
“…We have recently demonstrated that polysaccharides can be visualized around the coccolithophore C. braarudii using fluorescent dyes conjugated to lectins (Walker et al, 2018). In the present study, we use fluorescence microscopy to examine the extracellular polysaccharides associated with coccoliths in five coccolithophore species.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Coccolithus and Helicosphaera, and non-obligate calcifiers such as Emiliania huxleyi (Durak et al, 2016;Walker et al, 2018).…”
Section: Biogeochemical Implications Of Phenotypic Evolutionmentioning
confidence: 99%
“…In this issue of New Phytologist , Walker et al . (pp. 147–162) present a study that addresses the link between coccolith formation and cell biology.…”
mentioning
confidence: 99%